2015
DOI: 10.2298/mpns1512371m
|View full text |Cite
|
Sign up to set email alerts
|

Bone-patellar tendon-bone graft preparation technique to increase cross-sectional area of the graft in anterior cruciate ligament reconstruction

Abstract: For the average thickness (3-5 mm) and width (10 mm) of the patellar tendon graft, the cross-sectional area will be 30-50 mm2. The modified bone-patellar tendon-bone graft preparation technique made it possible to increase its cross-sectional area to 71-81 mm2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…1 Bone patellar bone tendon graft had problems regarding extensor loss, patellar fracture, loss of motion etc. 2 which led to the evolution of the hamstring graft using semitendinosus and gracilis tendons. Various implants have been described to hold the graft in the femoral and tibial tunnels, like suspensory devices, posts, screws, and suture buttons.…”
Section: Introductionmentioning
confidence: 99%
“…1 Bone patellar bone tendon graft had problems regarding extensor loss, patellar fracture, loss of motion etc. 2 which led to the evolution of the hamstring graft using semitendinosus and gracilis tendons. Various implants have been described to hold the graft in the femoral and tibial tunnels, like suspensory devices, posts, screws, and suture buttons.…”
Section: Introductionmentioning
confidence: 99%
“…Toritsuka et al [37] compared graft cross-sectional area and tunnel filling percentage between BTB and hamstring grafts from the same patient. The primary disadvantage of BTB grafts lies in the discrepancy between the graft and bone tunnel dimensions, resulting in incomplete tunnel filling [21]. Ideally, reconstruction involves positioning bone tunnels anatomically at the ACL attachment site while matching graft and native ACL geometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al [20] increased cadaveric BTB graft cross-sectional area by sectioning bone blocks longitudinally and folding the ligament. Tubularization of the graft, a technique published by the Clinic for Orthopedic Surgery and Traumatology, Clinical Center of Vojvodina, involves suturing the middle third of the femoral bone block to form a tube shape [21]. This technique significantly increased the cross-sectional area to 71-81 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The harvesting of PT as an autograft is considered a gold standard for ACL reconstruction. This study presents data on the morphometry of the harvestable area of PT which is suggested to be an important parameter to consider in preoperative surgical planning of ACL reconstruction when considering recovery and limb functionality at the donor and reconstruction sites [ 33 , 34 ]. An important step in the methodology of the present study is that the actual measurements ( in situ tendon tracing) were used to obtain a more realistic measurement [ 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%